Reciprocal Leadership Among Workers in the Directorate of the Iraqi Ministry of Youth and Sports from Their Point of View - Mohammed, Rawia Abdulfatah Atoof (Pubmedia Jurnal Pendidikan Olahraga, 2024)
The role of Reciprocal leadership is considered essential for those working in the Directorate of the Iraqi Ministry of Youth and Sports from their point of view, as they are responsible for achieving work goals and encouraging interaction within the institutional environment. Transactive leadership is a leadership style that depends on mutual interaction between the leader and employees in the organization, where emphasis is placed on the actual results of performance and linking reward to achievement, while relying on the principle of reward and punishment. This is done by assigning work to subordinates and correcting errors before they occur or taking corrective steps in the event of a mistake. As for the problem of the research, identifying the reciprocal leadership among workers in the Directorate of the Iraqi Ministry of Youth and Sports from their point of view. To achieve the goal of the research, the researcher prepared a reciprocal leadership questionnaire and included its paragraphs from (29) paragraphs distributed over three areas: the first area is conditional reward, the second area is conditional punishment, and the third area is management by exception, and it was distributed to them. The human area was composed of workers in the Directorate of the Iraqi Ministry of Youth and Sports, while the time area is between 1/23/2024 and 2024/4/23 As for the spatial field, the Directorate of the Iraqi Ministry of Youth and Sports, the descriptive approach was used, and the research community consisted of (36) workers. The main experiment was (30) workers in the Directorate of the Iraqi Ministry of Youth and Sports, from their point of view, and the exploratory experiment was (6) As for statistical processing, to analyze the data in this study, the statistical package was used SPSS. The researcher concluded that the attention and encouragement of workers in the Directorate of the Iraqi Ministry of Youth and Sports to reciprocal leadership because of its positive impact on the quality of the reciprocal relationship between the leader and subordinates and an important role in exercising effective leadership tasks. In light of the results, the study presented several recommendations, including developing a clear perception among workers in the Directorate. Ministry of Youth and Sports on the reciprocal leadership style based on exchanging rewards and punishment in exchange for work.